2023
DOI: 10.21203/rs.3.rs-2552766/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preference of Silicon Accumulation on the Shaded Foliage of Tree Crowns and its Implications for Juniperus chinensis L

Abstract: The passive accumulation of silicon (Si) generally depends on the regulation of plant transpiration rates. It is challenging to comprehend how plants use Si to adapt to shaded habitats where they have low transpiration rates. Therefore, we hypothesized that Si accumulation is partly due to physiological demand rather than being entirely dependent on transpiration regulation. To test this hypothesis, the concentrations of Si and total minerals at various positions of shaded foliage and branches within the crown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The heat and ROS generated by the NIR irradiation can synergistically suppress the growth of cancer cells. [44] In this study, Pd@MIL-100(Fe) showed photothermal effects that can inhibit the growth of cancer cells. Based on the previous study, these anticancer effects of Pd@MIL-100(Fe) and Pd@MIL-100(Fe)/polymer hybrids may be the outcome of both photothermal and photodynamic effects, as these effects usually occur simultaneously and cannot be separated.…”
Section: Photothermal Cytotoxicity Of Pd@mil-100(fe)/polymer Hybridsmentioning
confidence: 78%
“…The heat and ROS generated by the NIR irradiation can synergistically suppress the growth of cancer cells. [44] In this study, Pd@MIL-100(Fe) showed photothermal effects that can inhibit the growth of cancer cells. Based on the previous study, these anticancer effects of Pd@MIL-100(Fe) and Pd@MIL-100(Fe)/polymer hybrids may be the outcome of both photothermal and photodynamic effects, as these effects usually occur simultaneously and cannot be separated.…”
Section: Photothermal Cytotoxicity Of Pd@mil-100(fe)/polymer Hybridsmentioning
confidence: 78%
“…Therefore, we visualized response regions of our model to produce different localization maps visualized by CAM in images from 2 perspectives: (1) randomly selecting several cases, visualizing the region of interest (ROI), and (2) visualizing the self-learned multilevel (6 levels) features from shallow to deep layers. Our code for proposed Trisomy21Net has been made available in the Github repository …”
Section: Methodsmentioning
confidence: 99%